Dental students' OMFS‐related experiences and interest in OMFS careers: An exploration. Issue 4 (23rd December 2020) - Marti, Kyriaki C.; Tishko, Grayson; Edwards, Sean P.; Inglehart, Marita R.
Abstract: Purpose: While the numbers of oral maxillofacial surgery (OMFS) residents increased over time, women and residents from underrepresented minority backgrounds are still underrepresented. The objectives were to assess dental students' OMFS‐related personal and educational experiences and attitudes and explore which factors correlate with their interest in future OMFS careers. Methods: Data were collected from 493 dental students in 1 dental school and 206 students from 15 other US and Canadian dental schools. Results: The students in the national sample were more likely to have experienced an OMFS procedure themselves (64.6% vs. 50.7%; P  = 0.001), have shadowed an OMFS in an operating room (23.2% vs. 14.9%; P  = 0.009) prior to coming to dental school and to be much/very much interested in an OMFS career (36.4% vs. 12%; P  < 0.001) than the students at the home school. While the majority of both groups rated their experiences with rotations in the OMFS department in the dental school (68% vs. 62.5%) and in the hospital (80.3% vs. 85.7%) as very interesting, the students in the national sample were more likely to agree/strongly agree that they were satisfied with their OMFS experiences (68.1% vs. 36.3%; P  < 0.001) and had learned a lot from the OMFS faculty (57.9% vs. 30.8%) than the students in the home school. For both groups, the degree of interest in an OMFS career correlated with having had more personal OMFS experiences (home: r = 0.28; P  < 0.001/other: r = 0.39; P  < 0.001), more interesting OMFS experiences in the dental school (r = 0.23; P  < 0.05/r = 0.40; P  < 0.001) and the hospital (0.33; P  < 0.05/r = 0.50; P  < 0.001) and more positive attitudes toward OMFS faculty (r = 0.26; P  < 0.001/r = 0.37; P  < 0.001). Conclusions: Positive personal and educational OMFS experiences and positive attitudes toward OMFS faculty were associated with an interest in OMFS careers. These findings provide a basis for developing educational interventions aimed at increasing the percentage of women and residents from URM backgrounds in OMFS programs.